for this question, you are supposed to use this identity:
(x+a)(x+b)=x^2 + (a+b)x + ab and you have to do the "sum and product" method
---------------------------
4y^2+5y-9
=(2y)^2+2y( + )+( * )
here, we dont know what's a and what's b. what we know is :
a*b= -9
a+b= 5/2=2.5
thus, the larger no. is a positive no.
factors of -9 are : +1 or -1, +2 or -2, +4.5 or -4.5, +3 or -3
here we should do the 'trial and error' method.
a little experimentation will tell you that if we take 4.5 as a and -2 as b:
a*b= -9
a+b=2.5
thus,
(2y)^2+2y(4.5+(-2))+(4.5*-2)
=(2y+4.5)(2y+(-2)
=(2y+4.5)(2y-2)
this is the final answer
Checking:
(2y+4.5)(2y-2)
=(2y)^2 + 2y(4.5+(-2)) +(4.5*-2)
=4y^2 + 2y*2.5 + (-9)
=4y^2 + 5y - 9
2006-12-21 18:18:49
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
I'm assuming you want to solve for y:
4y² + 5y - 9 can be factored to (4y+9)(y-1)
Making that equal to 0 will allow you to solve for y (which in this case has 2 possible values)
(4y+9)(y-1) = 0
Therefore, either 4y+9 = 0 or y-1 = 0
solving for y gives you y = -9/4 & 1
2006-12-21 02:58:45
·
answer #2
·
answered by gamefreak 3
·
0⤊
0⤋
You want factorisation ?
4y^2 + 5y -9 = 4y^2 - 4y + 9y - 9 = 4y(y - 1) + 9 (y - 1) = (y - 1)(4y + 9)
2006-12-21 02:59:24
·
answer #3
·
answered by Srinivas c 2
·
0⤊
0⤋
Look again at your 1st answer.
5y = 9y - 4y
Substituting this into
4y^2 + 5y - 9 =
gives
4y^2 + 9y - 4y - 9 =
rearranging, you have
4y^2 - 4y + 9y - 9 =
factoring 1st & 2nd and 3rd & 4th terms,
4y(y - 1) + 9(y - 1) =
Collecting "coefficients",
(4y + 9)(y - 1)
2006-12-21 03:37:04
·
answer #4
·
answered by Helmut 7
·
1⤊
0⤋
4y^2 + 5y - 9
4y^2 + (-4 + 9)y -9
4y ( y - 1) + 9 (y -1)
(y - 1)(4y+9)
if solving for y:
(y - 1)(4y+9) = 0
y = 1, -9/4
2006-12-21 03:02:35
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
4y^2 + 5y - 9 = 4y^2 + 9y - 4y - 9 = 4y(y + 9) - 1(y + 9) = (4y - 1)(y + 9)
2006-12-21 02:58:01
·
answer #6
·
answered by N.math 2
·
0⤊
1⤋
4y^2 +5y - 9 = 4y^2 +( - 4y +9y) - 9 = 4y^2 -4y + 9y -9
= 4y(y-1) +9(y-1)
=(y - 1)(4y + 9)
2006-12-21 06:44:45
·
answer #7
·
answered by saudipta c 5
·
0⤊
0⤋
first multiply 4(the one before y^2) to -9 the answer is -36 then find the numbers that when you multiply will result to -39 but when you add will result to +5: that is -4 & +9, then replace 5y with -4y+9y..you will get 4y^2-4y+9y-9....then group similar___(i forgot what its called): (4y^2-4y)+(9y-9) then factor....4y(y-1)+9(y-1) but since (y-1) is similar to (y-1) (duh!) we will just consider it as one...which leaves us (4y+9)(y-1)....
got it?
2006-12-21 08:34:58
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
look kid as it as an quadratic equation
therfore it will be like this.
4y2+5y-9=0
4y2+9y-4y-9=0
y[4y+9]-1[4y+9]=0
[y-1][4y+9]=0
2006-12-21 07:55:01
·
answer #9
·
answered by kws 1
·
0⤊
0⤋
4y² + 5y - 9
4x² - 4y + 9y - 9
4x(y - 1) + 9(y - 1)
(4y + 9)(y - 1)
- - - - - - -s-
2006-12-21 04:24:53
·
answer #10
·
answered by SAMUEL D 7
·
0⤊
0⤋